2022
DOI: 10.1021/acsami.1c22569
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasensitive Analysis of Exosomes Using a 3D Self-Assembled Nanostructured SiO2 Microfluidic Chip

Abstract: Conventional microfluidics with a solid mixer for exosome detection is constrained by the low binding efficiency of the solid−liquid boundary effects and reduced sensitivity of individual markers. Here, we report a 3D-SiO 2 porous chip that combines nanoscale porous characteristics and multiple exosome specific markers to greatly improve the sensitivity for biosensing. The lower limit of detection was 220 particles/μL exosomes in PBS. We applied the 3D-SiO 2 porous chip for prostate cancer (PCa) staging in mic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 22 publications
0
19
0
Order By: Relevance
“…Similarly, a 3D-SiO 2 porous herringbone chip was constructed by Li et al through CSA technology for the multiplexed surface specific markers detection. 146 In this method, Tim-4 antibody-involved immunoaffinity was used to capture exosomes, and the biotinylated antibodies with the assistance of signal amplification strategy were applied to the detection of the four surface proteins (EpCAM, PSMA, and CD81). Clinical samples from prostate cancer staging and tumor-derived exosomes were analyzed by the 3D-SiO 2 porous chip with desirable sensitivity and specificity, respectively.…”
Section: D Porous Nanopatterned Microfluidic Chipmentioning
confidence: 99%
“…Similarly, a 3D-SiO 2 porous herringbone chip was constructed by Li et al through CSA technology for the multiplexed surface specific markers detection. 146 In this method, Tim-4 antibody-involved immunoaffinity was used to capture exosomes, and the biotinylated antibodies with the assistance of signal amplification strategy were applied to the detection of the four surface proteins (EpCAM, PSMA, and CD81). Clinical samples from prostate cancer staging and tumor-derived exosomes were analyzed by the 3D-SiO 2 porous chip with desirable sensitivity and specificity, respectively.…”
Section: D Porous Nanopatterned Microfluidic Chipmentioning
confidence: 99%
“…5D). 83 They simulated the fluid flow in their device and reported that presence of SiO 2 nanostructures (as compared to only herringbone structure) reduced fluid stagnation near the surface which subsequently led to enhanced affinity capture of sEVs through increased particle-surface interaction.…”
Section: Molecular Capturing Approachmentioning
confidence: 99%
“…5A). 100 They immobilized SiO 2 nanoparticles modified with Tim4 antibody in herringbone-shaped channels to capture exosomes. The captured exosomes were incubated with biotinylated detection antibody (anti-EpCAM, anti-PSMA, and anti-CD81).…”
Section: Detection Technologiesmentioning
confidence: 99%